Sustainable bio-jet fuel synthesis techniques for the aviation industry - Tan C.H.; Yaw C.T.; Koh S.P.; Kadirgama K.; Abed A.M.; Majdi H.S. (Institute of Physics, 2025)
In the near future, the aviation industry is expected to significantly increase the usage of "drop-in"bio-jet fuel as the technologies in biofuel production advances and matures. Given the high rate of growth in the aviation sector, the demand for aerial transportation of passenger and cargo is projected to increase by two-fold in the next twenty years. This will raise the global aviation fuel consumption to an estimated 22.48 quadrillion British thermal unit (BTU) by 2040. To meet these high energy demands, it is necessary to develop alternative and sustainable methods to produce jet fuel. In light of this, intense research and numerous fundings have been allocated into developing efficient production methods for bio-jet fuel. Conventional jet fuel emits a considerable amount of greenhouse gases (GHGs) when combusted, which contributes to global warming. Compared to traditional jet fuel, bio-jet fuel is a renewable energy source and regarded to emit less GHGs. Bio-jet fuel can be produced using a diverse range of both edible (food crops such as soybean, corn, and sugar cane) and inedible (such as energy crops, agricultural wastes, and lignocellulosic biomass) feedstocks. There are various promising technologies that can produce aviation biofuel, which includes oil-to-jet [hydroprocessed ester and fatty acids (HEFA)], alcohol-to-jet, sugar-to-jet [hydroprocessing of fermented sugars (HFS)], and syngas-to-jet [Fisher-Tropsch (FT)]. Compared to the other techniques, HEFA bio-jet fuel can be sold at a lower price because HEFA requires less capital investment, capital cost, and energy cost. Although FT technique require high capital investment, FT bio-jet fuel can be sold at medium price due to its matured technology. The breakeven cost of ATJ and HFS bio-jet fuel varies greatly due to the supply and cost of sugar-rich feedstocks, as well as short lifespan of enzymes. Although bio-jet fuel has the potential to replace petroleum jet fuel in the future, there are still many technological and socio-economic challenges that must be overcome. Therefore, this paper aims to highlight the current status, technological advances, and economic challenges of bio-jet fuel production for energy transition in the aviation industry. ? Published under licence by IOP Publishing Ltd.